Integrating Local Wisdom in Indonesian Language Learning: Effects on Engagement and Teaching Readiness of Pre-Service Elementary Teachers - Sitti Harisah; Mirnawati Mirnawati (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2026)
Indonesian language learning in teacher education remains predominantly text-oriented and insufficiently connected to students' local cultural contexts. This condition results in decontextualized learning experiences that inadequately support the engagement and pedagogical readiness of pre-service elementary and madrasah ibtidaiyah teachers. This study examines the influence of integrating local wisdom into Indonesian language learning on student engagement and teaching readiness, and the mediating role of engagement in this relationship. A quantitative survey design was employed, with data collected from 223 PGMI students selected through purposive sampling. Structural Equation Modeling-Partial Least Squares (SEM-PLS) analysis using SmartPLS revealed that local wisdom integration positively and significantly affected student engagement (? = 0.742) and teaching readiness (? = 0.391). Student engagement also significantly predicted teaching readiness (? = 0.487) and partially mediated the relationship between local wisdom integration and teaching readiness (? = 0.361). These findings indicate that culturally grounded Indonesian language instruction creates more contextual, participatory, and meaningful learning experiences for pre-service teachers. The study contributes to culturally responsive teacher education by demonstrating that integrating local wisdom is an effective pedagogical strategy for strengthening both student engagement and the professional readiness of future elementary and madrasah ibtidaiyah educators. However, as data were collected through self-reported questionnaires from a single institution with 223 participants, the generalizability of the findings warrants further investigation across diverse educational contexts.